TAMAN EDUKASI SEBAGAI RUANG PUBLIK DI KABUPATEN SINJAI - Nasda, Supriadi; Ersina, Sriany (Nature : National Academic Journal of Architecture, 2015)
The main problems that exist in urban areas that lack public space that can be utilized by the community as a place to socialize or interact with each other. Town hall is supposed to be public space is often used as residential land up with a business area such as malls etc. Shopping center in this case the mall, will never be considered as a public space because it is only accessible by people with a certain economic class. Sinjai in itself, the existence of public spaces in this case the city park, is still very alarming, the condition of the city park in Sinjai was not maintained so that people tend not to use the public space to the maximum in this case as a forum to interact with each other. As a solution to permalasahan, lack of public space in the city of Sinjai hence, the need for a city park that can be used to maximum people of the city and can be beneficial in terms of social, economic and environmental.